Removal of copper from industrial wastewater using spent coffee grounds - Akgün, Nalan A.; Bozkurt, Belgin; Salt, İnci (Yıldız Teknik Üniversitesi, 2013)
In the literature, several studies have been reported on the sorption of metal ions from contaminated water using natural materials including bamboo dust, coconut shell, etc. which is modified with the chemicals or pyrolyzed, in batch mode studies or column systems. Indeed, in these possible scenarios containing waters formulated, sometimes, pre-treatments increase the cost. Therefore, in this study, adsorption studies have been performed by different kinds of spent coffee grounds with moist (60-65%) to determine the efficacy of Cu(II) removal from original industrial wastewater whose initial metal ions 2.11 g/L at pH 11.04 in bench-scale packed column. Results depending on experimental design have shown that spent coffee grounds rapidly remove copper from waste water to below detection levels. Consequently, heavy metal removal using original spent coffee grounds would be an effective method for the economic treatment of wastewater.
Keywords: Industrial Biotechnology; Endüstriyel Biyoteknoloji